A Review of Total Hip Arthroplasty Comparison in FNF and OA Patients - Jakub Szczesiul; Marek Bielecki (Advances in Orthopedics)
Background. Worldwide, total hip arthroplasty (THA) has become one of the most commonly performed surgical procedures. Femoral neck fracture (FNF) and osteoarthritis (OA) are two of the medical conditions necessitating a hip replacement, most frequently carried out. The preoperative and postoperative pathways for patients suffering from these two diseases differ, yet worldwide, many national healthcare systems underestimate or misinterpret the (more than nuanced) care plan differences of the two. Factors and Criteria. Analyzed material was gathered from studies published between 2013 and 2019. Various strands of data demographics, comorbidities, and complications, as well as treatment outcomes, were tabulated to compare and contrast THA patients suffering from FNF and OA to collate their findings. Outcomes were cross-checked and validated for reliability and then were presented in a table format. Results. All five retrospective cohort studies fitted the required criteria for inclusion in this work, four US-based study groups and one European-based study group. Data were gathered from three separate databases. The “average” FNF patient is 76.8 years old. There was a 68.96% female probability. The “average” OA patient is 69.15 years old. There was a 5.24% female probability. 59.57% operated for athrosis, and only 34.63% operated for fracture which received grade lower than the third in the American Society of Anaesthesiologist (ASA) classification. There was more than 3 times higher prevalence of complications in the trauma group. FNF patients’ hospitalization was approximately 3 days longer. On average, 3.7% of patients operated for trauma and 1.5% of patients with elective THA required a second surgery. 6.57% FNF and 2.93% OA patients had unplanned readmission. Conclusions. In general, patients who suffer a femoral neck fracture are an extremely fragile group. They require additional perioperative and postoperative care. To meet these desired expectations, more FNF cost-comprehensive systems need to be initiated.